Lone Stars : A Legacy of Texas Quilts, 1986-2011 - Bresenhan, Karey 1942-; Puentes, Nancy O'Bryant.; Bresenhan, Karey, 1942- (Austin : University of Texas Press, 2011)
This volume, which covers 1986-2011, completes the landmark documentation of 175 years of Texas quilt history that the authors began in Lone Stars I and II.
Includes bibliographical references and index.
Keywords: Quilts -- Catalogs. -- History -- 20th century -- Texas; Quilts -- Catalogs. -- History -- 21st century -- Texas